A Note on Circular Distance Energy and Circular Distance Laplacian Energy - Kaladevi, V.; Bhuvaneshwari, R. (Journal of Informatics and Mathematical Sciences, 2017)
The circular distance energy of a simple connected graph \(G\) is defined as the sum of the absolute values of its eigen values of the circular distance matrix of \(G\). In this paper, the bounds for circular distance energy is obtained. Also the circular distance energy and the circular distance laplacian energy of certain graphs via circular distance energy are derived.